Efficacy and Toxicity of Stereotactic Radiotherapy Using CyberKnife in Patients of Vestibular Schwannoma: A Single Institutional Study - Shabbir, Saima Madiha; Mahmood, Humera (Biological and Clinical Sciences Research Journal, 2025)
Vestibular schwannoma (VS) is a benign tumor arising from the vestibulocochlear nerve, with management options ranging from microsurgical resection to stereotactic radiotherapy (SRT). CyberKnife (CK) offers frameless, image-guided stereotactic radiosurgery (SRS) or fractionated stereotactic radiotherapy (FSRT), providing conformal target coverage while minimizing toxicity to adjacent organs at risk (OAR). Objective: To evaluate the efficacy and toxicity of CK based SRS/SRT in VS via radiological response on MRI, symptom change (at 3,6 and 12 months interval), and OAR dosimetry at a single institution. Methods: This prospective observational study included 37 consecutive patients with radiologically or histopathologically confirmed VS treated with CK between December 2023 and December 2024. Baseline demographics, tumor characteristics, and treatment parameters were recorded. SRS was delivered in single fractions of 13–15 Gy, while FSRT was delivered in 3 fractions (21 Gy) or five fractions (20–22.5 Gy). Dosimetric parameters were assessed in accordance with the 2022 UK consensus guidelines. The primary endpoint was radiological tumor response at 6 and 12 months, assessed by MRI. Secondary endpoints included changes in presenting symptoms (hearing loss, headache, vertigo, tinnitus) and OAR dosimetry. Symptom improvement was analyzed using paired significance tests with α = 0.05. Results: The median age was 52 years (range 19–77), with a female predominance (64.8%). Laterality was left in 54.0%, right in 43.2%, and bilateral in one case. Mean tumor volume was 19.8 cm³ (range 0.53–73.9). Histopathological confirmation was available in 24.3% of cases. OAR analysis showed D0.035 cc (Dose to 0.035cc) to the brainstem of 7.2-9.9Gy for SRS and 19.8 ± 6.32Gy for FSRT and a mean ipsilateral cochlear dose of 2.8-3.7Gy for SRS and 14.29 ± 7.36 Gy for FSRT. At 6 and 12 months, no progressive disease was observed; stable disease was reported in 81.1% and 67.5% of patients, while partial responses were seen in 18.9% and 32.4%, respectively. A complete response was not achieved during the follow-up period. Composite symptom improvement was statistically significant (p = 0.0035). Conclusion: CK-based SRS/FSRT provided excellent early radiological control of VS with no progression at 12 months and significant improvement in symptoms, even in patients with relatively large baseline tumor volumes. Treatment was delivered within safe OAR dose limits, supporting CK as an effective modality for both short-term and long-term disease control. Extended follow-up is warranted to assess hearing preservation and long-term tumor control across fractionation schedules.